Engineering aligned electrospun PLLA microfibers with nano-porous surface nanotopography for modulating the responses of vascular smooth muscle cells. Issue 21 (7th June 2015) - Zhou, Qihui; Xie, Jing; Bao, Min; Yuan, Huihua; Ye, Zhaoyang; Lou, Xiangxin; Zhang, Yanzhong
<x xml:space="preserve">Abstract</x> Surface nanotopography in the form of elliptical nano-pores onto the aligned PLLA fibers allows for enhancing the biomimetic properties of the fibrous substrata by stimulating the vSMC functioning more effectively.